2003
DOI: 10.1159/000072814
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Inhibits TNF-α Synthesis More Effectively in Alzheimer’s Disease Patients than in Healthy Individuals

Abstract: Inflammatory mechanisms are involved in the pathogenesis of Alzheimer’s disease (AD). It is postulated that cytokine synthesis is altered in AD patients compared with nondemented subjects. Glucocorticoids play an important role in cytokine synthesis. We assessed the release of tumor necrosis factor-alpha (TNF-α), interleukin-10 (IL-10) and interleukin-12 (IL-12) and its regulation by dexamethasone in AD patients in vitro. Cytokine levels were measured using the ELISA method in unstimulated, LPS-stimulated or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Inflammation and glial activation in neurodegenerative diseases: AD Age is the major risk factor for AD (Katzman 1986). Epidemiological evidence (Dziedzic et al 2003;Sala et al 2003) as well as that obtained using experimental models of AD (Griffin and Mrak 2002;Melton et al 2003) show that pro-inflammatory conditions promote the development and progression of AD (Akiyama et al 2000;Lim et al 2000;Neuroinflammation Working Group 2000). Non-steroidal anti-inflammatory drugs decrease the risk of AD or delay its onset (Stewart et al 1997;Broe et al 2000;Etminan et al 2003).…”
Section: Microglial Cell Reactivity and Diseasementioning
confidence: 98%
See 1 more Smart Citation
“…Inflammation and glial activation in neurodegenerative diseases: AD Age is the major risk factor for AD (Katzman 1986). Epidemiological evidence (Dziedzic et al 2003;Sala et al 2003) as well as that obtained using experimental models of AD (Griffin and Mrak 2002;Melton et al 2003) show that pro-inflammatory conditions promote the development and progression of AD (Akiyama et al 2000;Lim et al 2000;Neuroinflammation Working Group 2000). Non-steroidal anti-inflammatory drugs decrease the risk of AD or delay its onset (Stewart et al 1997;Broe et al 2000;Etminan et al 2003).…”
Section: Microglial Cell Reactivity and Diseasementioning
confidence: 98%
“…Age is the major risk factor for AD (Katzman 1986). Epidemiological evidence (Dziedzic et al. 2003; Sala et al.…”
Section: Microglial Cell Reactivity and Diseasementioning
confidence: 99%
“…Pilot experiments were conducted with dexamethasone (10 µM) on LPS-challenged whole blood samples from AD patients and healthy subjects. The authors reported that dexamethasone was more efficient on AD samples vs. controls [168]. Interestingly, dexamethasone is commonly co-administered with thalidomide analogs in cancer treatment (see section 5.8 below) because a cumulative effect on inflammation reduction was noted during clinical trials.…”
Section: Strategies and Challenges Involving Central Tnf-α Signalimentioning
confidence: 99%
“…Interestingly, dexamethasone is commonly co-administered with thalidomide analogs in cancer treatment (see section 5.8 below) because a cumulative effect on inflammation reduction was noted during clinical trials. However, long term administration of corticoids often results in adverse events such as increased risks of infection, osteoporosis, and mental depression via alteration of the hypothalamic-pituitaryadrenal (HPA) axis [168, 169], limiting their potential to treat chronic disorders like AD.…”
Section: Strategies and Challenges Involving Central Tnf-α Signalimentioning
confidence: 99%
“…It has been proposed that the inflammatory response to A causes the neuronal damage in AD. Epidemiological evidence (Dziedzic et al, 2003;Sala et al, 2003) as well as experimental models of AD (Griffin and Mrak, 2002;Melton et al, 2003) show that pro-inflammatory conditions promote the development of AD. On the contrary, evidence from multiple casecontrol and population-based studies supported a roughly 50% reduction in AD risk after long-term use of non-steroidal anti-inflammatory drugs (NSAID) (Stewart et al, 1997;Broe et al, 2000;Etminan et al, 2003).…”
Section: Role Of Inflammation In Admentioning
confidence: 99%